Manajemen Pengawasan dan Evaluasi di Madrasah Aliyah - Saepuloh, Asep; Saepuloh (Jurnal Garasi Buku dan Obrolan Keilmuan, 2024)
This research aims to find out how monitoring and evaluation is managed in Islamic educational institutions. To find out more about this, the author conducted research at Madrasah Aliyah Persis Sindangkasih Ciamis. The method used in this research was descriptive qualitative. The results of this research describe the management of supervision and evaluation at Madrasah Aliyah Persis Sindangkasih, which is carried out by three components, namely the head of the foundation, the head of the madrasah and the madrasah supervisor from the ministry of religion. The chairman of the foundation supervises human resources, finances, completeness of infrastructure. The principal's supervision is carried out on teaching staff and educational staff in the form of monitoring the implementation of teaching and learning activities (KBM). Meanwhile, supervision by madrasah supervisors is academic and managerial supervision. The conclusion of this research confirms that monitoring and evaluation management is absolutely necessary in any institution, including Islamic educational institutions which are the object of the author's research. The more effective the supervisory management system, the more controllable the quality and quality of the institution will be. A multi-supervision system will create a more effective control system in monitoring performance quality. This has been proven through research that supervision of the educational service process by three supervisory components, namely supervision from the head of the foundation, the head of the madrasah and the madrasah supervisor from the government can increase the effectiveness of educational services by the institution to stakeholders, namely students and parents.